2022
DOI: 10.1002/jrsm.1587
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing evidence from the earliest studies to support decision‐making: To what extent could the evidence be reliable?

Abstract: In evidence‐based practice, new topics generally only have a few studies available for synthesis. As a result, the evidence of such meta‐analyses raised substantial concerns. We investigated the robustness of the evidence from these earliest studies. Real‐world data from the Cochrane Database of Systematic Reviews (CDSR) were collected. We emulated meta‐analyses with the earliest 1 to 10 studies through cumulative meta‐analysis from eligible meta‐analyses. The magnitude and the direction of meta‐analyses with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The findings indicated a positive effect on pain reduction for PBM vs. control groups, SMD 5 1.03, SE 5 0.22, 95% CI 5 [0.43-1.63], p 5 0.0089 (Figure 2). The 2 studies that evaluated time to return to play in number of days will be summarized in narrative because meta-analysis is not appropriate for 2 comparison groups (63). One study suggested that an aloe gel group returned the athlete to play quicker than the PBM group (3).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings indicated a positive effect on pain reduction for PBM vs. control groups, SMD 5 1.03, SE 5 0.22, 95% CI 5 [0.43-1.63], p 5 0.0089 (Figure 2). The 2 studies that evaluated time to return to play in number of days will be summarized in narrative because meta-analysis is not appropriate for 2 comparison groups (63). One study suggested that an aloe gel group returned the athlete to play quicker than the PBM group (3).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…The 2 studies that evaluated time to return to play in number of days will be summarized in narrative because meta-analysis is not appropriate for 2 comparison groups (63). One study suggested that an aloe gel group returned the athlete to play quicker than the PBM group (3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, to be included in the dataset, systematic reviews should have at lead one meta-analysis that compares the risk of harms of one medication intervention to active drugs or inactive controls (e.g., placebo, waitlist), and the meta-analysis should have at least five randomized controlled trials, with the 2 by 2 table data were available for each trial. We limited meta-analyses should have five and more trials to reduce potential random error since one of our sub-projects was to investigate the statistical performance of current evidence synthesis methods [4] . We set requirement on the 2 by 2 table data since it allows us to identify any potential data extraction errors and take steps to solving the errors [5] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%